Environmental friendly Sr2TiMoO6 double perovskite for high temperature thermoelectric applications. (15th March 2017) - Saxena, Mandvi; Tanwar, Khagesh; Maiti, Tanmoy
Abstract: Environmental friendly, non-toxic double perovskite Sr2 TiMoO6 (STM) ceramics were synthesized using solid-state reaction route for high temperature thermoelectric applications. XRD and SEM studies confirmed the presence of single-phase solid solution with highly dense microstructure, which were achieved by optimizing sintering temperature and atmosphere. Effect of sintering atmosphere on the structure of STM samples was studied. Rietveld refinement of XRD data confirmed cubic structure of this double perovskite with space-group Pm 3 ¯ m . Temperature dependent thermoelectric measurement showed that STM ceramics converted from p-type into n-type behavior around 550 K. Conductivity mechanism of this double perovskite was further explained by small polaron hopping model. Graphical abstract: